The age of first dental visit -A retrospective study - KEERTHANA, R.; P, JESSY; CHAUDHARY, MANJARI (The journal of contemporary issues in business and government, 2021)
Early regular dental care is an important step that every parent should be aware.The first dental visit should be shortly after the child’s first tooth erupts and not longer after one year. The study was aimed to assess the age of the first dental visit of a child. Data were collected retrospectively from the dental records of saveetha dental college in India. Only children attending their first dental visits with no previous dental experience were included in the study. Descriptive statistics, cross-tabulation analysis, and chi-squared tests were done.The results concluded that about 53% of the first dental visit was found to be 11-18 years of age with male children being addressed more. Parental compliance with the standard age for initial dental visitation recommended by the major dental academies is lacking.